Enhanced Strength and Ductility Due to Microstructure Refinement and Texture Weakening of the GW102K Alloy by Cyclic Extrusion Compression. Issue 8 (August 2016) - Lin, Jinbao; Wang, Xinyi; Ren, Weijie; Yang, Xuexia; Wang, Qudong
Abstract : The cyclic extrusion compression (CEC) was applied to severely deform the as-extruded GW102K (Mg–10.0Gd–2.0Y–0.5Zr, wt%) alloy at 350, 400, and 450 °C, respectively. The microstructure, texture, and grain boundary character distribution of the CECed alloy were investigated in the present work. The mechanical properties were measured by uniaxial tension at room temperature. The crack initiation on the longitudinal section near the tensile fracture-surface was investigated by high-resolution scanning electron microscopy (SEM). The result shows that the microstructure was dramatically refined by dynamic recrystallization (DRX). The initial fiber texture was disintegrated and obviously weakened. The 8-passes/350 °C CECed alloy exhibited yield strength of 318 MPa with an elongation-to-fracture of 16.8%, increased by 41.3% and 162.5%, respectively. Moreover, the elongation-to-fracture of the 8-passes/450 °C CECed alloy significantly increased more than 3 times than that of the received alloy. The cracks were mainly initiated at twin boundaries and second phase/matrix interfaces during tensile deformation. The microstructure refinement was considered to result in the dramatically enhanced of the strength and ductility. In addition, the texture randomization during CEC is beneficial for enhancing ductility. The standard positive Hall–Petch relationships have been obtained for the CECed GW102K alloy.